The performance evolution of antivirus security systems in ultradense cloud server using intelligent deep learning - G. Ramesh; V. Aravindarajan, V. Aravindarajan; J. Logeshwaran, J. Logeshwaran (BOHR Journal of Computational Intelligence and Communication Network, 2023)
When creating an antivirus, not only the latest security mechanisms are taken into account, but also the needs of users. That’s why this antivirus works together at high speed. The program interface allows it to choose the most optimal function. Free delivery allows a large number of users to rate this product. With the help of an intelligent deep learning model, a smart solution was proposed in this article to identify the security threats. It enables rapid detection and efficient treatment of polymorphic and encrypted viruses. Infected archives can now be detected when opened. This helps prevent its software from getting infected again. The program has the ability to create a confidence zone, which allows reducing the scanning time by creating a list of objects subject to scanning. This list should only contain sources that you are sure of. This application is designed to provide reliable protection for your computer. The proposed model allows it to protect its computer from all types of viruses and various Trojans, root kits, worms, and other malicious objects